COMPARING INTRAVITREAL AIR AND GAS FOR THE TREATMENT OF VITREOMACULAR TRACTION. Issue 11 (November 2020) - Gruchociak, Sophie; Djerada, Zoubir; Afriat, Mickael; Chia, Valen; Santorini, Melissa; Denoyer, Alexandre; Arndt, Carl
Abstract : Purpose: To compare the effect of intravitreal injections of air with gas on vitreomacular traction (VMT) release and attempt to analyze predictive factors for success. Methods: The medical records of patients with symptomatic VMT undergoing intravitreal injections (0.3 mL) of either octafluoropropane (C3 F8 ) or air were retrospectively reviewed. The VMT release (primary end point) and the best-corrected visual acuity (secondary end point) were noted 1 month after injection. At baseline and 1 month after the injection, a macular optical coherence tomography was performed. Results: Twenty-four eyes of 22 patients were included. Vitreomacular traction was released in 10 cases, 7 among 11 C3 F8 -injected eyes (63%) and 3 among 13 air-injected eyes (23%) ( P = 0.045). In eyes with released VMT, ETDRS improved from 61 ± 35 (0–100) to 65 ± 37 (0–100) 1 month after the injection ( P = 0.03). All patients with VMT release had a horizontal vitreomacular adhesion of less than 600 µ m. Five eyes (23%) underwent vitrectomy after the injection of gas or air. Conclusion: Posterior vitreous detachment in VMT can be observed with both air and gas injection with a low complication rate. The occurrence of VMT release observed with air seemed to be less frequent than that observed with gas. Abstract : Intravitreal injections of octafluoropropane (C3 F8 ) appeared to be more effective than air to release vitreomacular tractions and to significantly improve visual acuity with few complications.